Pegylated Liposomal Doxorubicin Versus Epirubicin as Adjuvant Therapy for Stage I–III Breast Cancer - Hu, Wenxian; Lv, Kezhen; Teng, Rongyue; Chen, Jida; Xu, Chenpu; Jin, Lidan; Chen, Yongxia; Zhao, Wenhe (Frontiers in Genetics, 2021)
Background: Conventional anthracyclines, like epirubicin, are cornerstone drugs for breast cancer treatment of all stages, but their cumulative toxicity could cause life-threatening side effects. Pegylated liposomal doxorubicin (PLD), an effective anti-breast cancer drug, has lower toxicity than conventional anthracyclines. This retrospective study compared the efficacy and toxicity profiles between PLD and epirubicin as adjuvant therapy for breast cancer. Patients and Methods: A total of 1,471 patients diagnosed with stage I–III breast cancer between 2000 and 2018 were included in this study, among which 661 were treated with PLD and 810 with epirubicin, with 45.9 months as the median follow-up time. Anti-breast cancer efficacy was assessed with overall survival (OS) and disease-free survival (DFS), while cardiac toxicity was assessed with left ventricular ejection fraction (LVEF) and electrocardiogram (ECG). Results: The Kaplan–Meier method and Cox proportional hazards model revealed that there was no statistical difference in OS or DFS between patients treated with PLD and epirubicin, regardless of cancer stages or molecular subtypes (all p-values > 0.05). In addition, patients had significantly better LEVF and ECG data after adjuvant therapy with PLD (both p-values < 0.05). Conclusion: Based on the large sample size and the long follow-up time of this study, we conclude that PLD has a similar anti-breast cancer efficacy as epirubicin while inducing lower level of cardiac toxicity in Han Chinese. This study suggests that PLD-based adjuvant chemotherapy could be a better option than epirubicin for breast cancer patients especially with existing cardiac disease.